Magia neopentecostal e "espírito" neoliberal - Abreu, Nayara dos Santos (2017)
The purpose of this research is to find the possibilities of affinity between Neo- Pentecostalism and neoliberalism through the observation of the Universal Church of the Kingdom of God (1977), with the cult of entrepreneurs as a cut. Although most of the Universal’s faithful don’t own companies, the speech emphasizes that everyone must have an entrepreneurial vision. Such a religion offers magic-religious services in an attempt to solve problems that should be a priority and the responsibility of the State, such as the lack of jobs, the treatment of diseases, and the list goes on. And as the "new spirit of capitalism" demands that, the individual be more and more detached, courageous and audacious in the Neopentecostal faith, such characteristics are also required from the faithful. The church is managed as an enterprise, which adapts to capitalism by being dynamic and flexible and constituting a large market for religious goods; applying the neoliberal governmentality in the relationship between the individual and the faith, reason of its great success